Leadership leadership and teaching performance in a parish educational institution in the district of San Isidro. - Arana Agûero, Laura Morayma (2017)
The research aims to determine the relationship between the styles of management leadership and teacher performance at school in San Isidro. The design it was used the correlacional and the instrument it was used the leadership directive questionnaire and this was made by Paz H. and Zamora C. (2014). It was applied to all the 48 teachers of the school. In order to measure the teacher performance were taken into account the evaluations that were obtained from the Academic Management department of the institution. The results showed that there is a direct and significant relationship between these two variables, point out that the most predominant style is the Transformational Leadership, and there is a high level of performance of teachers of the school.